Discharging Batu Bara pada PLTU Rembang dengan Convensional Dibandingkan Conveyor sebagai Bahan Bakar Pengolahan Semen Di Pt. Semen Indonesia - Sutini Sutini (Jurnal Universal Technic, 2022)
This research is mainly aimed at improving the way of discharging coal at PLTU Rembang, which is one of the power plant business units of a subsidiary of PT PLN located in Sluke District, Rembang Regency, Central Java Province. It maps the dimensions of the discharging speed using conveyor and grape . Data collected through surveys to coal shipping companies are regressed in the Linear Regression model. The results show that two characteristics of discharging services with conveyors and grapes affect time and cost (1) The duration of coal discharging (2) The cost of coal discharging. using qualitative and quantitative primary and secondary by direct observation to the field and data collection then the data is processed using multiple linear regression, the targeted outputs are national journals, national seminars, monographs.